Evaluasi Pelaksanaan Perkuliahan dan Hasil Belajar Mahasiswa pada Pembelajaran Daring dan Luring di Fakultas Ilmu Olahraga Unesa - Faridha Nurhayati; Ika Jayadi; Irma Febriyanti; Panji Bana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study will examine the evaluation of student learning and learning outcomes in online and offline learning at the Faculty of Sports Science. The research method used is comparative, which is to compare the results of lecture evaluations and learning outcomes. Sampling technique with purposive sampling, with a total of 274 students. Data analysis techniques using t-tests. The results showed that the average implementation of online learning was in the good category (56.2%) and the average offline learning was in the good category (59.1%). Conclusion There is no significant difference in the implementation of online learning and the learning outcomes of online and offline learning in Faculty of Sports Science Universitas Negeri Surabaya students. Key word: Evaluation, Learning, online, offline, learning outcomes